Developing the Flood Forecasting system and operationalizing integrated flood risk management measures in the Zambezi basin - Umer, Yakob; Padhee, Suman; Amarnath, Giriraj (2024)
Strengthening the FFEWS system and operationalizing integrated flood risk management measures in the Zambezi basin Established Flood Forecasting and Early Warning (FFEWS) framework that includes a review of open-source models, data availability, operationalizing capacity, and its scalability.